Pembelajaran Akhlak Melalui Pendekatan Kontekstual dalam Membentuk Karakter Religius - Hidayati, Ratna; Abdillah, Nanang (Faidatuna, 2025)
Islamic Religious Education is a subject aimed at fostering noble character and instilling spiritual values in students. One indicator of the success of our education system is the success in strengthening faith and piety as well as cultivating noble character. The nobility of character and morals is a tangible measure of the goals of national education. However, the reality is that Islamic Religious Education in schools today is more bound to the school system, which is more focused on teacher-centered learning approaches. Educators play a vital role in achieving the desired learning outcomes in the teaching and learning process. Meanwhile, students act as both subjects and objects in applying the contextual teaching and learning method. Teachers can use various methods to convey information to students (transfer knowledge), whether it is related to teaching materials or global perspectives. The process of knowledge transfer through conventional methods can no longer be sustained, as society expects students to be intelligent and responsive to the times, not merely passive observers and listeners. The breakthrough offered by education experts is a new concept called contextual teaching and learning (CTL). This method is not merely about transferring knowledge from teacher to student but also empowers students to engage, experiment, and reconstruct the material they learn from the teacher, correlating it with their real-life experiences. The hope is that they can solve various problems in their lives, families, and communities. This research focuses on three aspects: character education, religious character, and character education through a contextual approach aimed at forming religious character. Based on this discussion, the objective of this paper is to understand: Character Education, Religious Character, and Character Education through a Contextual Approach in shaping Religious Character. This research employs a qualitative approach using a literature study.